COVID-19 with high-sensitivity CRP associated with worse dynamic clinical parameters and outcomes - Iam-Arunthai, Kunapa; Chamnanchanunt, Supat; Thungthong, Pravinwan; Chinapha, Anongnart; Nakhahes, Chajchawan; Suwanban, Tawatchai; Umemura, Tsukuru (Frontiers in Medicine, 2024)
Objective This study aimed to evaluate the relationship between high-sensitivity C-reactive protein (hsCRP) in hospitalized COVID-19 patients and their clinical outcomes, including trajectory of hsCRP changes during hospitalization. Method and results Patients with positive COVID-19 tests between 2021 and 2023 were admitted to two hospitals. Among 184 adult patients, approximately half (47.3%) had elevated hsCRP levels upon admission, which defined as exceeding the laboratory-specific upper limit of test (> 5.0 mg/L). Clinical outcomes included critical illness, acute kidney injury, thrombotic events, intensive care unit (ICU) requirement, and death during hospitalization. Elevated hsCRP levels had a higher risk of ICU requirement than those with normal, 39.1% versus 16.5%; adjusted odds ratio (aOR), 2.3 [95% CI, 1.05–5.01]; p = 0.036. Patients with extremely high (≥2 times) hsCRP levels had aOR, 2.65 [95% CI, 1.09–6.45]; p < 0.001. On the fifth day hospitalization, patients with high hsCRP levels associated with acute kidney injury (aOR, 4.13 [95% CI, 1.30–13.08]; p = 0.016), ICU requirement (aOR, 2.67 [95%CI, 1.02–6.99]; p = 0.044), or death (aOR, 4.24 [95% CI, 1.38-12.99]; p = 0.011). The likelihood of worse clinical outcomes increased as hsCRP levels rose; patients with elevated hsCRP had lower overall survival rate than those with normal (p = 0.02). The subset of high hsCRP patients with high viral load also had a shorter half-life compared to those with normal hsCRP level (p = 0.003). Conclusion Elevated hsCRP levels were found to be a significant predictor of ICU requirement, acute kidney injury, or death within 5 days after hospitalization in COVID-19 patients. This emphasized the importance of providing more intensive care management to patients with elevated hsCRP.